IDENTIFIKASI SENYAWA KIMIA DAN PENELUSURAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOLIK DAUN TUMBUHAN TEROMPET UNGU - Eva Monica (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Petunia  (Ruellia  brittoniana  Leonard) is a  wild  plant  species belonging  to  the Acanthaceae family. This study aimed to identify the content of ethanolic extract of petunia leaf. A total of 185 grams of petunia  leave powder were macerated with ethanol resulting 17.5 grams of ethanolic  extract.  Chemical  identification  was  performed by  using  reagents.  The  test  using reagents showed that the extract contains tertiary alkaloid, polyphenol, saponin, and essential oil. The antioxidant activity of the extract was recorded by using DPPH assay with the value of ES54 was 53,39 µg/mL. Keywords: Ruellia brittoniana, Acanthaceae, extract, antioxidant.